Assessment of Lipid Profile among Sudanese patients with Type 2 Diabetes Mellitus - Mohamed, Rania Ali Abdalla; Noor, Bakri Yousif Mohammed; Ahmed, Shamseldein Mohmed; Dafalla, Abuagla M.; Mohammed, Yousif abdelhameed; Modawe, GadAllah Osman (AL-Kindy College Medical Journal, 2022)
Background: Diabetes mellitus is a major health issue that is one of the leading causes of cardiovascular disease. Recent studies have found a link between uncontrolled diabetes and cardiovascular disease, with dyslipidaemia predicting glycated-hemoglobin (HbA1c), which could be a major contributor to type 2 diabetes complications and etiology.Objectives: The objective of present study was estimate lipid profiles among control and uncontrolled type 2 diabetic patients.Subjects and Methods: Analytical case control based study, One hundred twenty participate were included in study, 70 patients with DM  as case group  refer to Abuagala Center and difference follow up diabetic center  and 50 non diabetic subjects taken as control group males and females their  age between 20 to 80 years. Fasting blood glucose (FBG), blood HbA1c, and serum lipid parameters were measured by CobseC311 from Roche instrument. Data was analyzed using SPSS version 22, which expressed as (mean±SD) with p.value.Result:Among120 participant the levels of fasting blood glucose,blood HbA1c,and Triglyceridewereincreased significantly in T2DM (161.7±72.5mg/dl), (8.88±3.9 %), (121±61.9 mg/dl)when compare with control group(91.28±13.9), (5.7±0.50), (80±11.7) with P.value (0.000),while total Cholesterol, High Density Lipoprotein, and Low Density Lipoprotein were not significant different in T2DM when compared with control group. There was weak positive correlation between HbA1c with FBG, CHOL, LDL, and HDL (r = 0.207, P =0.089, r = 0.186, P =0.124, r = 0.167, P =0.168, r = 0.308, P =0.01) respectively, while TG hadweak negative correlation (r =- 0.146, P =0.228). Conclusion: The results indicated to considerable increase in the lipid profile levels in type two diabetic patients when compared with healthy controls group which may lead to increase in coronary risk factors.